2021
DOI: 10.3390/healthcare9070870
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death in Adults: A Practical Flow Chart for Pathologist Guidance

Abstract: The medico-legal term “sudden death (SD)” refers to those deaths that are not preceded by significant symptoms. SD in apparently healthy individuals (newborn through to adults) represents a challenge for medical examiners, law enforcement officers, and society as a whole. This review aims to introduce a useful flowchart that should be applied in all cases of SD. Particularly, this flowchart mixes the data obtained through an up-to-date literature review and a revision of the latest version of guidelines for au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 159 publications
(165 reference statements)
5
41
0
1
Order By: Relevance
“…These new genetic techniques not only improve the accuracy of forensic determination of AASs as the cause of death but could help the scientific community to understand some of the aspects related to AASs abuse that are still unknown. A recent review confirmed the pivotal role of genetic investigation in the case of SCD [60]. Moreover, several recent studies reported the importance of research in the field of new molecular biomarkers such as miRNAs [23,91].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These new genetic techniques not only improve the accuracy of forensic determination of AASs as the cause of death but could help the scientific community to understand some of the aspects related to AASs abuse that are still unknown. A recent review confirmed the pivotal role of genetic investigation in the case of SCD [60]. Moreover, several recent studies reported the importance of research in the field of new molecular biomarkers such as miRNAs [23,91].…”
Section: Discussionmentioning
confidence: 74%
“…Tseng et al [59] conducted a study about out-of-hospital cardiac arrest (OHCA) and sudden cardiac death (SCD). To verify if the out-of-hospital deaths were due to cardiac causes, autopsy with histological and toxicological investigations were performed, as it was recently suggested to ascertain the exact cause of death in suspected SCD [60]. A multidisciplinary commission judged the final cause.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, 3D CNN algorithms can automatically evaluate not only hard-tissue structures and search for inapparent damage that could have been responsible for a sudden death incident [91,130].…”
Section: Overview Of Used Artificial Intelligence For Forensic Age and Sex Determinationmentioning
confidence: 99%
“…Observer defines the points, and their interobserver error are the main weakness of cephalometric analysis (Figure 6). Anthropometry in Forensic Medicine and Forensic Science is frequently used for sex and biological age determination and other purposes [129][130][131].…”
Section: Artificial Intelligence Implementation In 3d Cephalometric Landmark Identificationmentioning
confidence: 99%
“…One explanation could be that they are the ones that are more easily obtained even on the black market or through a friend, for example, at school or university. In addition, the easy administration (oral or inhalation) also contributes to ease of consumption [1,6,8,12]. The main reasons for the increase of smart drug use/abuse were: improvement of cognitive functions, reduction of stress, increase in free time, and increase in school and work performance [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%